Metals removal techniques from wastewater: a literature review (Research, Society and Development, 2022)
Due to the growth of the industries, the generation of effluents with metals grows sharply, generating losses on the fauna and flora. Concern about the fate of the metals generated led to the development of methods for removing pollutants from wastewater. The present study reviews the advances in removal techniques in recent years. In this work, the removal of metals was evaluated from the perspective of the adsorption processes (components of the fluid phase are transferred to the surface or pores of a solid phase, thus removing the adsorbate molecules), biosorption (ion binding of the molecules in solution that bind to functional groups present on the surface), electrodialysis (transport of ions through ion exchange membranes through a difference in electrical potential as a driving force), reverse osmosis (a membrane is designed to allow water to pass through, while retaining solutes ), ultrafiltration (separation of metal ions by a membrane filtration process), chemical precipitation (combination of addition of coagulant followed by pH adjustment), precipitation by sulphide (use of the sulphide as a precipitant of the metal ions present), biomineration (microorganisms facilitate extraction and recovery of metals) and bioleaching (solubilization of metals and recycling due to the action of oxidizing microorganisms).